Damage to civil liability for aircraft accidents - محمد, محمد صديق (Journal of Legal Sciences, 2017)
That it is reasonable to assume that the repossive damage is the result of tort liability, but this has raised in our minds the question of the extent to which the damage arising from the liability may arise, not only from tort liability, and from the possibility that the damage is direct and not indirect, It is possible to try to prove that the injured person can be compensated for recidivism as a result of the realization of contractual liability in general, with a focus on achieving the contractual liability of the air carrier in particular.Consequently, the study has worked to clarify the intentional damage to aircraft accidents and to distinguish between the liability of the carrier to the passenger as the original victim of the aircraft accidents and the carrier's responsibility towards the victim of the return, thereby indicating the independence of both of these responsibilities vis-à-vis the air carrier. Through the study, we attempted to clarify the conditions for compensation for damage caused by aircraft accidents and to indicate the discretionary power of the judge in the persons involved in the liability for the damage.In addition, the provisions of the repossessed damage in aircraft accidents were clarified and therefore the extent of the possibility of amending the provisions of liability and their effect on the repossessing damage, whether in tightening or mitigating it, was clarified. Finally, it was necessary to clarify the means of compensation for the damage to the most appropriate means of this damage, Moral damage is apostasy. Based on the above, the subject was dealt with by dividing it into a preliminary section that highlights the legal organization of air transport and then two sections. The first topic is entitled "Defining the damage caused by aircraft accidents". The second topic is the provisions of repetitive damage in aircraft accidents. Pre-requisite: - Legal regulation of civil liability for air transport the first topic: - Defining the damage caused by aircraft accidents The second topic: - The provisions of the damage in the aircraft accidents Conclusion